PENGARUH MEDIA WAYANG KERTAS TERHADAP KEMAMPUAN MENYIMAK CERITA SISWA KELAS II SDN 116 PEKANBARU - Abi Rivaldi; Febrina Dafit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The lack of media use in learning Indonesian, especially story material, causes students to be less interested in the lesson. Resulting in low listening skills of students because they do not understand the teacher's explanation of the story content. This study was written with the aim of determining the influence of paper puppet media on the ability to listen to stories of class II students at SDN 116 Pekanbaru. This quasi-experimental study used a Non Equivalent Control Group Design. The number of respondents was 71 people. The data collection instrument in this study used a formative test or multiple-choice test. The results of the study showed that paper puppet learning media had an influence on the ability to listen to stories of students at SDN 116 Pekanbaru. The results of the Independent-Sample T-Test with a sig. (2-tailed) value of 0.019 <0.05, then Ho was rejected and Ha was accepted. With the use of paper puppet media, the average value of the experimental class was greater than the control class. The learning outcomes of the experimental class were better than the control class. This shows that there is an influence between the effectiveness of paper puppet media on the ability to listen to stories.